2020
DOI: 10.3892/ol.2020.12405
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of lncRNA‑associated ceRNA network reveals the novel potential of lncRNA, miRNA and mRNA biomarkers in human rectosigmoid junction cancer

Abstract: Although accumulating evidence has confirmed the potential biological functions of long non-coding RNAs (lncRNAs) as competitive endogenous RNAs (ceRNAs) in colorectal tumorigenesis and progression, few studies have focused on rectosigmoid junction cancer. In the present study, a comprehensive analysis was conducted to explore lncRNA-mediated ceRNA implications and their potential value for prognosis. lncRNA, microRNA (miR/miRNA) and mRNA expression profiles were downloaded from The Cancer Genome Atlas databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Park et al reported that the clinicopathological characteristics of the rectosigmoid junction cancer are similar to those of sigmoid or rectal cancer, but the rectosigmoid junction cancer has different patterns of lymphatic spread compared to the sigmoid colon or rectum cancer and more frequently metastasizes to the pararectal nodes ( 13 ). The distinctive RNA network of the rectosigmoid junction has also been reported ( 21 , 22 ). A recent study reported that the rectosigmoid junction had a deviant behavioral pattern compared to the patterns of adjacent bowel segments, including lower 5-year overall survival and higher lymph vascular invasion ( 35 ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Park et al reported that the clinicopathological characteristics of the rectosigmoid junction cancer are similar to those of sigmoid or rectal cancer, but the rectosigmoid junction cancer has different patterns of lymphatic spread compared to the sigmoid colon or rectum cancer and more frequently metastasizes to the pararectal nodes ( 13 ). The distinctive RNA network of the rectosigmoid junction has also been reported ( 21 , 22 ). A recent study reported that the rectosigmoid junction had a deviant behavioral pattern compared to the patterns of adjacent bowel segments, including lower 5-year overall survival and higher lymph vascular invasion ( 35 ).…”
Section: Discussionmentioning
confidence: 80%
“…A previous study also revealed that the sigmoid-rectal region appears to have unique molecular features compared to those of other colon-sided locations ( 20 ). The distinctive competing endogenous RNA and long non-coding RNAs of the rectosigmoid junction cancer have been reported ( 21 , 22 ). A multi-omics study of gastric cancer has also demonstrated the heterogeneity of molecular features ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, if all four databases concur on a specific miRNA as a potential target, it is retained as the designated targeted miRNA [ 28 ]. Additionally, we utilized the spongeScan database to anticipate the lncRNAs that target the binding of miRNAs and assigned names to the identified targeted lncRNAs [ 29 ]. Lastly, to depict the regulatory network involving circRNA-miRNA-mRNA, we employed Cytoscape software for visualization purposes.…”
Section: Methodsmentioning
confidence: 99%
“…MiRNAs bind to partially complementary sequences of target gene transcription products, which are known as response elements (MREs). Endogenous RNA with the same MREs can competitively bind to miRNA, which is called competitive endogenous RNA (ceRNA) [ 7 , 8 ]. LncRNAs, cirRNAs, and pseudogenes can compete with miRNA for the same miRNA response elements and reduce miRNA inhibition, increasing the expression of miRNA target genes (mRNA) [ 7 , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous RNA with the same MREs can competitively bind to miRNA, which is called competitive endogenous RNA (ceRNA) [ 7 , 8 ]. LncRNAs, cirRNAs, and pseudogenes can compete with miRNA for the same miRNA response elements and reduce miRNA inhibition, increasing the expression of miRNA target genes (mRNA) [ 7 , [9] , [10] , [11] ]. CeRNA is a novel regulatory mechanism in cancer, which is attracting widespread attention and is involved in many biological processes, including epithelial-mesenchymal transition (EMT), proliferation, apoptosis, metastasis, and chemoresistance [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%